Theoretical Aspects in regard to the Regulation of Evidence in the Civil Lawsuit - Cristinel- Ioan Murzea (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2020)
In our currently used language, the word evidence represents the logical-mental operation by which we attempt to prove something, to demonstrate, to emphasize a certain statement that provides credibility to a particular situation. The institution of evidence in objective law was differently regulated in material law as opposed to procedural law, depending on the different factors which configured private law, but also in direct connection with the lawmaker’s interest. Thus, the current Civil Code no longer contains regulations regarding evidence in antithesis with the 1864 Civil Code; however the institution is regulated in the new Civil Procedure Code, namely law no. 134/2010 regarding the Civil Procedure Code, which would later be republished with subsequent changes. As a consequence, the institution is currently studied in Civil Procedure Law, whereas, before this new regulation, it was studied within the general theory of Civil Law.